2009
DOI: 10.1007/978-3-642-03584-5_3
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoskeleton as a Nanoscale Information Processor: Electrical Properties and an Actin-Microtubule Network Model

Abstract: One of the major goals of nanotechnology is to advance the field of information processing. The central processing units of the future are likely to be quite different from those currently used. While biomolecular processors are unlikely to displace semiconductor processors for speed and accuracy, certain proteins may offer solutions to problems confronting logical processor design, including self-assembly and emergent computation. Cytoskeletal proteins may prove useful as biomolecular processors or may inspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 134 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…MT possibly interacts with cortical actin network to determine stationary or migratory state of the cell [ 2 ]. Especially, MT is important in neuron cells, where it forms neural tubes, determines the position of axon, and participates in early neurite differentiation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…MT possibly interacts with cortical actin network to determine stationary or migratory state of the cell [ 2 ]. Especially, MT is important in neuron cells, where it forms neural tubes, determines the position of axon, and participates in early neurite differentiation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the main elements of the cytoskeleton (microtubules and microfilaments), in addition to their structural role in cell shape and movement, have the capacity to conduct ions [45,46,47,48,49]. This seems likely to be a potential mechanism of signal transmission [47,49], but the biological role for this conduction has not been clearly demonstrated. We propose that, while much the information received at the membrane can be processed locally to produce only a local response, some signals may require a global cellular response and, thus, must be disseminated to the nucleus and other organelles.…”
Section: Information Transmission Within Cellsmentioning
confidence: 99%
“…More generally, physical systems may be applied to mathematical problems to create machines and computers. Complex systems may be correspondingly abstracted in algorithmic terms in order to describe phenomena that have traditionally evaded the grasp of understanding, such as complexity arising from biological sensorial-actuation networks, through which phenomena such as 'intelligence' are hypothesised to emerge [1,2,3,4,5,6,7], even in organisms that do not possess nervous systems [8]. This application of computing concepts and development of experimental devices therein encompasses the field of 'unconventional computing'.…”
Section: Introductionmentioning
confidence: 99%